A Radiative Transfer Modeling Methodology in Gas-Liquid Multiphase Flow Simulations - Gautham Krishnamoorthy; Rydell Klosterman; Dylan Shallbetter (Journal of Engineering)
A methodology for performing radiative transfer calculations in computational fluid dynamic simulations of gas-liquid multiphase flows is presented. By considering an externally irradiated bubble column photoreactor as our model system, the bubble scattering coefficients were determined through add-on functions by employing as inputs the bubble volume fractions, number densities, and the fractional contribution of each bubble size to the bubble volume from four different multiphase modeling options. The scattering coefficient profiles resulting from the models were significantly different from one another and aligned closely with their predicted gas-phase volume fraction distributions. The impacts of the multiphase modeling option, initial bubble diameter, and gas flow rates on the radiation distribution patterns within the reactor were also examined. An increase in air inlet velocities resulted in an increase in the fraction of larger sized bubbles and their contribution to the scattering coefficient. However, the initial bubble sizes were found to have the strongest impact on the radiation field.